2005
DOI: 10.1002/jbm.b.30320
|View full text |Cite
|
Sign up to set email alerts
|

Adhesive layer properties as a determinant of dentin bond strength

Abstract: The goal of this study is to evaluate the hypothesis that the properties of the resin adhesive might affect the microtensile bond strength (MTBS) of multibottle dental adhesive system. In order to alter the properties, the experimental resin adhesives containing 2,2-bis (4-2-hydroxy-3-methacryloyloxypropoxyphenyl)propane (Bis-GMA) and triethylene glycol dimethacrylate (TEGDMA) at various ratios were prepared. Degree of conversion immediately after curing (DC-immed), degree of conversion at 48 h after curing (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0
7

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 48 publications
1
51
0
7
Order By: Relevance
“…There is a known solvent concentration at which maximum conversion is reached, more or less solvent than this amount can decrease monomer conversion, 27 which seems related to the viscosity of the adhesive film. 24 Although not measured in this study, it was visually evident that OSP is far more fluid than SBP. Thus, one can assume that the remaining water from the wet bonding technique could have been beneficial to the SBP by increasing the flowability of the adhesive, enlarging the mobility of the reactive components during polymerization and resulting in increased nanohardness values.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…There is a known solvent concentration at which maximum conversion is reached, more or less solvent than this amount can decrease monomer conversion, 27 which seems related to the viscosity of the adhesive film. 24 Although not measured in this study, it was visually evident that OSP is far more fluid than SBP. Thus, one can assume that the remaining water from the wet bonding technique could have been beneficial to the SBP by increasing the flowability of the adhesive, enlarging the mobility of the reactive components during polymerization and resulting in increased nanohardness values.…”
Section: Discussionmentioning
confidence: 60%
“…[21][22][23] The current investigation does not agree with the first hypothesis raised by Dal-Bianco and others 15 and Reis and others. 16,24 It only agrees with the second. If higher water/solvent evaporation had occurred, one would expect high nanohardness and Young's modulus values at the adhesive layer when the adhesive was vigorously applied in the dry environment.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…When Bis-GMA was used in fractions of more than 60 wt% in a Bis-GMA/TEGDMA mixture, that is, less than 40 wt% TEGDMA, autodeceleration of the polymerization reaction decreased the DC owing to the increased viscosity in the adhesive mixtures. 4 However, in the Bis-M-GMA/TEGDMA mixture, a decrease of TEGMDA content to 20 wt% had no influence on the DC of the experimental adhesive due to low viscosity of Bis-M-GMA. Although the molecular weight of Bis-M-GMA is greater than that of Bis-GMA, Bis-M-GMA is relatively free from diffusion limitations due to the absence of hydrogen bonds.…”
Section: Discussionmentioning
confidence: 94%
“…2 Improvement in the mechanical properties of the adhesive layer is an important factor in increasing dentin bond strength. 3,4 There were various efforts to increase the mechanical properties of the adhesive layer; loading fillers, increasing the degree of conversion and improving the monomer system. It was suggested that adding fillers to the adhesives would increase the mechanical strength of the adhesive layers.…”
Section: Introductionmentioning
confidence: 99%